Pengamatan Karakteristik Strain Cordyceps militaris (L) tipe liar alam dari lima perkebunan kelapa sawit di Muara Wahau Kalimantan Timur - Edwin Aprianda; Gunawan Djajakirana; Darmawan Darmawan (Jurnal Penelitian Kelapa Sawit, 2021)
Cordycep militaris (L) is known in oil palm plantations as a natural enemy of nettle caterpillars. This fungus infects the caterpillars that descend down to become pupae around the palm circle, so that the pupae do not develop into imago and the pest's life cycle will be interrupted. This fungus is one of the 3 main entomopathogenic fungi used as bioinsecticides to control pests in oil palm plantations. In this study, the characteristics of C. militaris were observed from 5 oil palm plantations cultured in vitro using two types of media and two incubation methods. The results showed that there were mycelium pigmentation in nutrient-rich media Sabouraud Dextrose Agar plus Yeast extract (SDAY) when incubated with lighting. Only one of five mycelium cultures using SDAY media showed pigmentation on the no-light incubation method. Pigmentation did not occur in nutrient-poor media such as agar (WA), either incubated with lighting or with no-light. The growth of isolates was generally higher on SDAY media than on WA media. This study showed that C. militaris is a facultative phagotrophic fungus. The highest growth of isolates cultured on SDAY media incubated with lighting was found in isolates A and C, with colony diameter 90 mm, high mycelium density (+++) and hairy texture like cotton at the end of the 3rd week after inoculation. In the no-light incubation method, the highest growth was found in isolates B and C with colony diameter 90 mm, high mycelium density (+++) and hairy texture like cotton at the end of the 3rd week after inoculation. Isolates A and C showed high virulence potential to be used as bioinsecticides.